2019
DOI: 10.1186/s10033-019-0340-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electrical Characteristics of Inter-wire Arc in Cross-Coupling Arc

Abstract: As a new composite welding heat source introduced in recent years, the cross-coupling arc uses a non-consumable electrode arc (plasma arc) and a consumable electrode arc (inter-wire arc) in cross-coupling, in which the plasma arc is the main arc and the inter-wire arc is the vice arc, to realize the separate control of the heat input to the workpiece, arc force, and droplet transfer. To reveal the electrical characteristics of the inter-wire arc under the action of the plasma arc, in this study, rotating probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…In this method, a variable polarity arc can be established between two wires by loading a variable polarity welding supply to a tandem GMAW system. Lu et al [23] proposed cross-coupling arc welding, which can decouple the heat and mass transfer by cross coupling a GTAW arc and GMAW arc. In this process, one arc is formed between the tungsten electrode and base metal, while the other one is formed between the two wires.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, a variable polarity arc can be established between two wires by loading a variable polarity welding supply to a tandem GMAW system. Lu et al [23] proposed cross-coupling arc welding, which can decouple the heat and mass transfer by cross coupling a GTAW arc and GMAW arc. In this process, one arc is formed between the tungsten electrode and base metal, while the other one is formed between the two wires.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the research on cross-coupling arc welding mainly focuses on arc stability, arc behavior, and droplet transfer [20,21,22,23,24], especially arc stability tests playing a primary role in the development of welding processes, which is an important mean to determine whether the arc can perform effective thermal output and whether the droplet transition is stable [25,26]. However, it is found that there is an obvious polar zone phenomenon in the study of cross-coupling arc stability, that is, the main arc is regularly inclined to the polar zone of the IWA.…”
Section: Introductionmentioning
confidence: 99%